6(1+2m)+m=71

Simple and best practice solution for 6(1+2m)+m=71 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(1+2m)+m=71 equation:


Simplifying
6(1 + 2m) + m = 71
(1 * 6 + 2m * 6) + m = 71
(6 + 12m) + m = 71

Combine like terms: 12m + m = 13m
6 + 13m = 71

Solving
6 + 13m = 71

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 13m = 71 + -6

Combine like terms: 6 + -6 = 0
0 + 13m = 71 + -6
13m = 71 + -6

Combine like terms: 71 + -6 = 65
13m = 65

Divide each side by '13'.
m = 5

Simplifying
m = 5

See similar equations:

| (8n+56)-(2n+14)= | | 7r^2+10=80 | | 2x+9(2)+1x-5(2)=50 | | 6(2x+7)=78 | | 1672.992=2*3.14*51.84+2*3.14*7.2*h | | 15319=525+.0575(15319-30000) | | 6(r-5)=-66 | | y=-x(-6) | | 3z^2+17+20=0 | | 3x+2x+5x+5=40 | | 10(x-4)=50 | | 7-7x=7x+5x | | -5(5x-3)+4x=120 | | (5x+6)(7x+7)= | | 2a^2-4=126 | | bx-1=63 | | X-y=c(X) | | 4x+14=9x-35 | | 2y^2+6y+5=0 | | 2(m+3)=4m-k | | 7x-6=-2x+3 | | 9-5x^2=-71 | | 11x+2=14x-7 | | y=2x+1(X) | | 2(2x-4)=-20 | | 94.9536=20.3472+11.304h | | 15-(-42)= | | 880=2n^2-4n | | 1672.992=2*3.14*r^2+2*3.14*7.2*h | | 5(x+7)-6(x+6)=0 | | N^2=8n-16 | | t=2m(m) |

Equations solver categories